Wuestman, Eric A., "Sowing Supply: Compensating Responses by Rural Coca Economics to Intervention in the Cocaine Market" (System Dynamic Society Records, 1990)
In recent years, increased public awareness of the health and productivity costs associated with the use of cocaine and its potent derivative “crack” has served to heighten concern and renew debate over the most effective strategies for managing the drug problem. This paper presents a preliminary system dynamics model of the international cocaine trade. The initial model incorporates the various stages of the cocaine system from source country production to final consumption including: primary resource allocation and production; cocaine production; cocaine production and export; and U.S. demand, import, pricing, and consumption. The model is used to examine an ensemble of policies proposed by the National Strategy for Drug Control (White House 1989). Simulation results show the capacity of the system to exhibit a wide array of behavior modes depending on the type of intervention being applied and the aspect of the problem being targeted. Of particular interest from a policy standpoint is the implication of delays in physical and information flows for generating divergent short and long term policy results. Findings suggest a comprehensive approach combining demand and supply side policy leverage represents the most effective management strategy.